Tinjauan Penurunan Konsolidasi Tanah Lempung Kecamatan Sukodono Yang Distabilisasi Dengan Garam Dapur (NaCl) - Mujiwati, Sri Endah, Qunik Wiqoyah, S.T., M.T, Agus Susanto, S.T, M.T (2017)
Based on the result of Atterberg limits test Sukodono's soils has plasticity index value PI = 51,77%, which means clay soil with high plasticity, therefore it is necessary to be repaired. In this research, chemically improvements have done by adding salt (NaCl) with percentage of addition 5%, 10%, 15%, and 20% of the sample weight. The methods of analysis in this research include physical properties test, standard Proctor test and consolidation test on original soil and mix soil. The result of physical properties test shows that the bigger percentage addition of NaCl water content value, plastic limit, shrinkage limit rise, while the specific gravity value, liquid limit, plasticity index and passing sieve No. 200 decrease. The result of standard Proctor test, the maximum value of dry weight increase and the optimum moisture content value decrease along with the addition of NaCl. Maximum value of dry volume weight is 1,368 g/cm3 and the lowest optimum water content is 24,3% on mix soil with the addition of 20% NaCl. The result of consolidation test shows that the bigger percentage of NaCl addition, the coefficient of consolidation value (Cv) increase, while compression index value (Cc) and settlement of consolidation (Sc) decrease. Cv value of the original soil is 0,0158 cm2/sec, Cc value is 0,2961 and Sc value of 0,1183 cm. The highest Cv value is 0,0194 cm2/sec, the lowest Cc value is 0,2320 and the lowest Sc value is 0,0917 cm obtained on the mix soil with addition percentage 20% of NaCl. Keywords : clay soil, consolidation, physical properties, salt (NaCl).